1992
DOI: 10.1212/wnl.42.1.255
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral disappearance of parkinsonian signs after subthalamic hematoma

Abstract: A man with Parkinson's disease (PD) suddenly developed a left hemiballismus, and the CT showed a hematoma of the right subthalamic nucleus. After the ballistic movements had disappeared, akinesia and the other parkinsonian signs did not reappear on the left. This clinical case confirms the involvement of the subthalamic nucleus in the akinesia of PD, as suggested by recent experimental data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(29 citation statements)
references
References 0 publications
0
28
1
Order By: Relevance
“…Unilateral lesions involving the STN and adjacent tissue are associated with dyskinesias characterized by hemiballism in the monkey (Whittier and Mettler, 1949;Carpenter et al, 1950;Hamada and DeLong, 1992). Furthermore, lesions of the STN ameliorate the symptoms of experimentally induced parkinsonism in monkeys (Bergman et al, 1990) as well as clinical parkinsonism in humans (Sellal et al, 1992). We recently have shown, however, that the relationship between SN and STN in the monkey (Dybdal et al, 1997) may be very different from the relationship in the rat (as shown here) or cat (Murer and Pazo, 1993); accordingly, there is a need for caution in the extrapolation from rodent models to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Unilateral lesions involving the STN and adjacent tissue are associated with dyskinesias characterized by hemiballism in the monkey (Whittier and Mettler, 1949;Carpenter et al, 1950;Hamada and DeLong, 1992). Furthermore, lesions of the STN ameliorate the symptoms of experimentally induced parkinsonism in monkeys (Bergman et al, 1990) as well as clinical parkinsonism in humans (Sellal et al, 1992). We recently have shown, however, that the relationship between SN and STN in the monkey (Dybdal et al, 1997) may be very different from the relationship in the rat (as shown here) or cat (Murer and Pazo, 1993); accordingly, there is a need for caution in the extrapolation from rodent models to humans.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, iron deposits in the subthalamic nuclei, revealed by cranial MRI, beside an iron-related pallidal diffuse T2-weighted hypointensity in HS has not been reported up to now. The subthalamic iron deposits in our subject may influence the clinical symptomatology of HS, because case reports describe disappearance of parkinsonian signs after subthalamic spontaneous hemorrhage or hemotoma [8, 9]. Iatrogenic lesioning of the subthalamic nucleus abolishes the excitatory drive from the subthalamic nucleus to the globus pallidus, followed by improvement of parkinsonian signs and appearance of severe and permanent dyskinesia [10].…”
Section: Discussionmentioning
confidence: 99%
“…Striatal dopamine loss is postulated to result in increased striatal inhibition of GPe, which in turn results in disinhibition of STN and increased basal ganglia output from GPi. This concept is supported by the fact that STN inactivation results in a substantial reduction of the severity of parkinsonian motor signs in monkeys (Bergman et al, 1990;Guridi et al, 1993;Baron et al, 2002) and human patients (Sellal et al, 1992;Gill and Heywood, 1997;Alvarez et al, 2001).…”
Section: Global Neuronal Activity Changes In Parkinsonismmentioning
confidence: 95%